An Interrelated decisions Model - Haramoto Nishikimoto, Edwin (Revista INVI, 2001)
The paper proposes the implementation of an interrelated decision making system which allows to overcome the problems faced by the agents taking part in the working areas related to the housing action. Four models are thus described (housing, decision, information and housing alternatives) which enable the ordering , relating , grouping and setting hierarchies for all the components of the housing process.